Post-traumatic brain injury agitation and disinhibition after a motor vehicle accident: A difficult choice for patient, carer and primary team - Mohd Amiruddin Mohd Kassim; Pang, Nicholas Tze Ping; Ng, Jun N. (Edizioni Minerva Medica, 2021)
A young man became increasingly aggressive and irritable following an acute frontoparietal hemorrhage and craniectomy. Subsequently he developed sexual disinhibition 4 days post injury. There were no other psychotic, mood or neurotic symptoms and there were no features of delirium. There was no history of substance intoxication or withdrawal preceding the accident. He was initially treated with atypical antipsychotics which helped alleviate the irritability and agitation. However due to the evolving sexual disinhibition, he was switched to mood stabilizers which brought his symptoms to remission. This case report illustrates the plethora of potential symptoms following traumatic brain injuries, which could be dynamic and distressing to caregivers and doctors. Serial imaging, mapping of lesion sites to potential symptoms and anatomic correlates and judicious use of symptom-appropriate medication was vital in order to manage such patients.